Antisolvent‐ and Annealing‐Free Deposition for Highly Stable Efficient Perovskite Solar Cells via Modified ZnO. Issue 13 (7th May 2021) - Wang, Ziyu; Zhu, Xuejie; Feng, Jiangshan; Wang, Chenyu; Zhang, Cong; Ren, Xiaodong; Priya, Shashank; Liu, Shengzhong (Frank); Yang, Dong
Abstract: Even though ZnO is commonly used as the ETL in the perovskite solar cell (PSC), the reactivity of perovskite deposited thereupon limits its performance. Herein, an ethylene diamine tetraacetic acid‐complexed ZnO (E‐ZnO) is successfully developed as a significantly improved electron selective layer (ESLs) in perovskite device. It is found that E‐ZnO exhibits higher electron mobility and better matched energy level with perovskite compared to ZnO. In addition, in order to eliminate the proton transfer reaction at the ZnO/perovskite interface, a high quality perovskite film fabrication process that requires neither annealing nor antisolvent is developed. By taking advantages of both E‐ZnO and the new process, the highest efficiency of 20.39% is obtained for PSCs based on E‐ZnO. Moreover, the efficiency of unencapsulated PSCs with E‐ZnO retains 95% of its initial value exposed in an ambient atmosphere after 3604 h. This work provides a feasible path toward high performance of PSCs, and it is believed that the present work will facilitate transition of perovskite photovoltaics in flexible and tandem devices since the annealing‐ and antisolvent‐free technology. Abstract : The highest efficiency of 20.39% is obtained for perovskite solar cells based on modified ZnO without annealing and antisolvent process. The perovskite devices exhibit unprecedented environmental stability owing to efficient decreased organic ligands on ZnO surface.